A VALIDATED RP-HPLC METHOD FOR THE DETERMINATION OF SPARFLOXACIN IN BULK AND PHARMACEUTICAL DOSAGE FORM - RAVISANKAR, P.; DEVADASU, CH.; RAO, G. DEVALA; RAO, M. NAGESWARA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To develop a simple, accurate, precise and selective isocratic reversed phase-high performance liquid chromatography (RP-HPLC) method was developed for the quantitative estimation of Sparfloxacin in pharmaceutical formulations. Experimental: RP-HPLC method was developed by using Welchrom C18 Column with 250 mm x 4.6 mm i.d and 5µm particle size, SHIMADZU LC-20AT Prominence liquid chromatograph. The mobile phase used is phosphate buffer (pH-3.0): acetonitrile (70:30percent v/v) with a flow rate of 1mL/min. The eluent was monitored by UV detection at 291nm using SHIMADZU SPD-20A prominence UV-Vis detector. Results: The retention time of Sparfloxacin found to be 5.499 min. The method retains linearity in the range of 2-10µg/mL with correlation coefficient 0.9999. The mean recovery of sparfloxacin was 99.702percent to 100.456percent. The LOD and LOQ of the drug were found to be 0.186 µg/mL and 0.558 µg/mL respectively. Conclusion: The proposed method can be successfully used for routine determination of sparfloxacin in pharmaceutical formulations. KEY WORDS: Sparfloxacin, Isocratic RP-HPLC, Correlation coefficient , Method Validation.